Paleostress analysis and reconstruction of tectonic stress variations since Gondwana breakup in the Island Belt Fault Zone, Kutch Basin, India. (March 2023) - Jani, Chirag; Bhandari, Subhash; Kothyari, Girish Ch.; Lakhote, Abhishek; Chauhan, Gaurav; Thakkar, M.G.
Graphical abstract: Highlights: The Island Belt Fault Zone (IBFZ) records multiphase deformation events. The IBFZ of Pachham and Khadir uplift demark distinctive stress patterns and zones. Crosscutting relationship of faults defines the superposition of stress in the IBFZ. Reconstructing paleostress data determine four major tectonic events in the IBFZ. Abstract: The Kutch Rift Basin (KRB) is a paleorift basin formed during the Gondwana breakup between the Indian and African plates that involved multiple deformational events. The present study demarks paleostresses induced during these deformational phases using paleostress inversion method and reconstructed the tectonic evolution of the Island Belt Fault Zone (IBFZ) situated in the Island Belt Uplift (IBU) (Pachham, Khadir, Bela and Chorar Uplift) in the northern KRB. The IBFZ comprises several faults, from which 145 distinct fault-slip data were used for paleostress analysis. In addition, the geometry of the cross-cutting fault planes and their induced paleostresses were correlated to reconstruct the relative timing of the deformational events in the IBFZ. The results were further associated with the known global events and with data from the literature to form an evolutionary model of the IBFZ. The present research determines paleostress induced during four major deformational events in the IBFZ region as: (a) extensional rifting phase followed by a transitional transtensional phase, (b) rift failure and compressional phase during basin inversion, (c) transitional transpressional phase, and (d) the Reunion hotspot magmatic and compressional phase during India-Eurasia collision.